Authoritarian setback in the current crisis of Brazilian democracy (Tempo e Argumento, 2021)
The article analyzes the democratic crisis experienced by Brazil from the second decade of the 21st century onwards. The aim is to investigate how this historical period can be characterized. The text asserts that it is inappropriate to understand Brazil without observing its historical distrust of democracy and lack of commitment to the rule of law. The research is based on the assumption that Brazilian modernization in the transition from the 20th to the 21st century was ambiguous but with important achievements. However, the authoritarian mentality and the gap in terms of the quality of political participation are factors of structural permanence. The hypothesis is that Brazil is experiencing a specific moment characterized by the awakening of an authoritarian and conservative mentality that impacts both the State and civil society. The research methodology is based on a bibliographical discussion, with contributions in history, political science, and law. The subjects are discussed in theoretical terms to understand the problems related to the political participation gap, the inequality between citizens, the difficulties of civic culture (mainly in the digital environment), and some inherent weaknesses in democratic performance. Starting from the idea that civic culture influences institutions and these, in turn, impact civic culture, Brazil is currently experiencing a political and cultural setback. Contrary to what could be imagined a few years ago, the process of Brazilian social modernization is threatened in its most important achievements, which implies a danger to the values ​​that sustain democracy.Keywords: authoritarianism; brazilian democracy; political culture; political participation; the rule of law.